1989
DOI: 10.1902/jop.1989.60.12.664
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of New Attachment Apparatus Formation in Humans

Abstract: Part I of this three-part human study evaluated the formation of a new attachment apparatus (bone, cementum, and periodontal ligament) on pathologically exposed root surfaces in an open and closed environment. The most apical level of calculus on the root served as a histologic reference point to measure regeneration on root surfaces exposed to the oral environment. Attempts were made to initiate the formation of a new attachment apparatus by flap curettage, root planing, coronectomy, and submersion of vital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
163
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(166 citation statements)
references
References 19 publications
2
163
0
1
Order By: Relevance
“…The study did not have non graft site as control group because numerous studies have been reported statistically significant results in favor of bone replacement grafts as compared to non-grafted site (Bowers et al 1989b;Mellonig 1992;Cortellini and Bowers 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The study did not have non graft site as control group because numerous studies have been reported statistically significant results in favor of bone replacement grafts as compared to non-grafted site (Bowers et al 1989b;Mellonig 1992;Cortellini and Bowers 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal/endodontic regeneration has been demonstrated with both FDBA and DFDBA, although one report from Dragoo and Kaldahl showed FBDA healing by repair (33)(34)(35). In an animal study, FDBA or DFDBA was placed into surgically created infrabony defects and evaluated histologically (36).…”
Section: Allograftsmentioning
confidence: 99%
“…Histological evidence further demonstrates that DFDBA grafts support the formation of a new attachment apparatus in intrabony defects, (Bowers et al 1989;Reynold et al 2003). They regenerate cementum, periodontal ligament, and bone (Bowers et al 1989) as opposed to mere open flap debridement which usually results in periodontal repair characterized primarily by the formation of a long junctional epithelial attachment (Reynold et al 2003).…”
mentioning
confidence: 94%
“…The bone grafts form a scaffold for the host's resident cells to grow through a process known as creeping substitution (Bodner 1995). Some grafts like demineralized freezedried bone allograft (DFDBA), in addition to osteoconduction also have osteoinductive properties due to the presence of osteogenetic factors (Bowers et al 1989).…”
mentioning
confidence: 99%